Magneto-dynamic tool for full arch immediate loading in post-traumatic restoration with narrow implants: A case report - Gabriele Cervino; Luca Fiorillo; Nicola Scotti; Francesco Alessandro Motta; Francesco Maria Motta; Jacopo Colombo; Artak Heboyan; Domenico Baldi (SAGE Open Medical Case Reports, 2024)
New surgical techniques using narrow, tilted implants positioned through a magneto-dynamic tool in guided surgery for a Toronto restoration. A 69-year-old woman wanted fixed rehabilitation to replace her removable complete dentures. A cone-beam computed tomography showed significant bone resorption in both the maxillary and mandibular regions. The plan was to load the entire upper arch with six implants immediately, while removable partial dentures were recommended for the lower jaw. The guided surgery project was aligned with the new dentures, and the laboratory created a printed cast with dental implant analogues in planned positions. A metal-reinforced denture was constructed, and surgery was performed to place six narrow implants using the magneto-dynamic instrument. The denture was directly screwed onto multi-unit abutments. Final rehabilitation was completed after 6 months. Narrow implants can be a good option for fixed, full-arch rehabilitations. Further research is needed to confirm these findings on a larger scale.